Planetary atmospheres - Taylor, FW (Oxford University Press, 2010)
The emphasis of this book is on comparative aspects of planetary atmospheres, generally meaning comparison with the Earth, including atmospheric composition, thermal structure, cloud properties, dynamics, weather and climate, and aeronomy. The goal is to look for common processes at work under different boundary conditions in order to reach a fundamental understanding of the physics of atmospheres. As part of a general Physics course, the material is chosen to emphasise certain aspects that will be of broad topical interest: - evolutionary processes, setting the Earth in its context as a planet and a member of the Solar System - the properties of atmospheres that affect the climate near the surface of each planet - measurement techniques and models, where the same experimental and theoretical physics is applied under different conditions to investigate and explain atmospheric behaviour. These might be thought of as the astronomical, environmental, and technical sides of the discipline respectively.